The Sosialisasi Peran Pola Asuh Orang Tua Sebagai Upaya Peningkatan Pemahaman Warga Desa Nglaban Melalui Posyandu Balita Desa Nglaban - Durrotunnafisa, Durrotunnafisa; Rosy, Brillian (LP2M STAI Darul Kamal NW Kembang Kerang-NTB, 2023)
The role of parenting is an important thing in shaping a child's personality. Every parent has a different parenting style. There are 3 types of parenting styles, namely authoritarian parenting, democratic parenting, and permissive parenting. There needs to be socialization about the role of parenting to increase parents' understanding of child care. Therefore, Unesa KKN-T Group 28 conducted outreach at the Toddler Posyandu in Nglaban Village. The method used is community education through outreach activities at the Toddler Posyandu in Nglaban Village. This socialization activity is expected to increase parents' understanding of supporting children's growth and development as a form of improving the quality of human resources.